Knowledge, attitudes, and practices toward biologics among systemic lupus erythematosus patients: a cross-sectional study - Xu, Xue; Du, Mengru; Lai, Peng; Zhao, Zhiling; Geng, Linyu; Liang, Jun; Chen, Haifeng; Sun, Lingyun (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the knowledge, attitudes, and practices (KAP) toward biologics among systemic lupus erythematosus (SLE) patients.MethodsA cross-sectional study was conducted at Nanjing Drum Tower Hospital from March 2023 to January 2024. Demographic information and KAP were obtained through the distribution of self-designed questionnaires.ResultsA total of 543 SLE patients participated in this study, with a mean age of 39.14 ± 13.08 years. The mean scores for knowledge, attitude, and practice were 6.08 ± 5.49 (possible range: 0–32), 33.14 ± 4.01 (possible range: 10–50), and 12.06 ± 3.95 (possible range: 6–30), respectively. Multivariate logistic regression analysis revealed that knowledge score (OR = 1.08, 95% CI: 1.019–1.144, p = 0.009), attitude score (OR = 1.476, 95% CI: 1.337–1.63, p < 0.001), average monthly income of 5,000–10,000 Yuan (OR = 2.129, 95% CI: 1.327–3.416, p = 0.002), and average monthly income of more than 10,000 Yuan (OR = 2.245, 95% CI: 1.184–4.260, p = 0.013) were independently associated with proactive practice. Structural equation modeling revealed significant direct effects of knowledge on attitude (β = 0.586, p < 0.001) and practice (β = 0.140, p = 0.041). Additionally, attitudes were found to directly influence practice (β = 0.628, p < 0.001).ConclusionSLE patients demonstrated inadequate knowledge, suboptimal attitudes, and passive practices regarding biologics. It is recommended that healthcare providers prioritize education and interventions aimed at enhancing knowledge, fostering positive attitudes, and promoting proactive practices regarding biologic therapies among SLE patients.